MARGINALIZATION OF FISHERMEN FROM UTILIZING COASTAL AREA AFTER RECLAMATION AT SERANGAN SUBDISTRICT, DENPASAR, BALI - Suryawan, Nyoman (E-Journal of Cultural Studies; Volume 7, Number 1, February 2014, 2014)
Geographically, Serangan Subdistrict, South Denpasar District, Bali Province, used to be separated from the Bali’s mainland. However, now it is not isolated any longer after a bridge was constructed and reclamation was conducted by the Bali Turtle Island (abbreviated to BTID) in 1996. At that time 379 hectares of the coastal areas were victimized. The investor’s existence and the other businesses utilizing the coastal areas as their operating areas physically changed them, which were entirely coastal. It was this which was directly and indirectly responsible for marginalizing the fishermen. In relation to that, how the fishermen at Serangan subdistrict were marginalized from utilizing the coastal areas after being reclaimed was the focus of the present study. Qualitative method and the approach of cultural studies were used in the present study. The data were collected through observation, in-depth interview, and documentary study. The data were descriptively, qualitatively and interpretatively analyzed.   To sum up, the present study showed that there were several forms of marginalization undergone by the fishermen at Serangan Subdistrict after reclamation; they were marginalized from utilizing the coastal environment; economic difficulty resulting from the fact that the sources of fish were getting scarce causing their income to go down; and their powerlessness in overcoming the problem they encountered to improve their standard of living.
Keywords: marginalization, fishermen, utilization of the coastal areas, after reclamation.